Evaluasi Tingkat Pengetahuan Perawat tentang Terapi Stimulasi Fisik pada Hiperbilirubinemia Neonatus - Eni Rahmawati; Dian Susmarini; Meivita Dewi Purnamasari (Journal of Bionursing, 2020)
Background. Infants with hyperbilirubin have management in lowering bilirubin levels. Management of the physiological management of jaundice is regular drinking with frequent breastfeeding and light therapy if possible. WHO guidelines for the pathological management of jaundice can be carried out by phototherapy and pharmacology. Physical stimulation therapy is a complementary therapy in the form of passive Range of Motion (ROM) movements. The aim of the study was to evaluate the level of knowledge of nurses about physical stimulation therapy in hyperbilirubinemia neonates. Methods. This study used a quasi-experiment with a one-group pretest-posttest design approach. The research was conducted in May-August 2020 in virtual or online due to the Covid 19 pandemic situation. The number of respondents was 30 people. Data collection using a modified questionnaire by the researcher. The data were then processed and analyzed using univariate analysis and bivariate analysis using the Paired Sample T-Test. Results. The mean pre-test score was 77.18 and the post-test mean score was 93.74. The statistical test results showed a difference in knowledge before and after education with a p-value of 0.000 (p <0.05). Conclusion. Nurses' level of knowledge about physical stimulation therapy increased after being given an education.